Pendampingan Posyandu Remaja Sebagai Upaya Preventif Kenakalan Remaja Di Surabaya - Alinea Dwi Elisanti; Efri Ti Ardianto (STIKes Hang Tuah Pekanbaru, 2021)
The transition period from childhood to adulthood often causes teenagers to experience problems. This period occurs between the ages of 10 to 19 years and is not married. The Indonesian Society of Dermatology and Venereology (INSDV) report the number of sexually transmitted diseases (STDs) for adolescents in Indonesia was increased from 2017. The exposure of adolescents to STDs can be triggered by juvenile delinquency such as premarital sexual relations, drugs, free sex which has an impact on pregnancy out of marriage, dropping out of school, early marriage, abortion, risk of childbirth, STDs. Efforts to anticipate juvenile delinquency are through the establishment of the Youth Integrated Service Post (YISP). It is part of the CAE program (Children, Adolescents and Elderly), as the flagship program of the Ministry of Health, and implemented at the Surabaya City Health Office. This program puts forward a preventive approach because it focuses on primary health care activities holistically. This program is the collaboration with the Benowo Public Health Center (PHC), Surabaya City Government, which aims to foster YISP through health education to solve problems during puberty. This activity was attended by 24Â youth assisted by the Benowo PHC. Health education activities were provided through a combination lecture method with the visual education method (documentary video screening), and at the end of the activity, the evaluation of adolescent knowledge was carried out. The results of community service activities showed that the adolescents have increased knowledge about how to deal with problems at puberty, and the best score of 90. Similar coaching activities can be used as preventive measures carried out on an ongoing basis and can be developed towards regular health screenings specifically STDs for teenagers. ABSTRAK Periode peralihan dari masa anak ke masa dewasa sering menyebabkan remaja mengalami masalah. Periode ini terjadi antara umur 10 sampai 19 tahun dan belum kawin. Laporan Perdoski menyatakan jumlah penyakit menular seksual (PMS) pada remaja di Indonesia terus mengalami peningkatan dari tahun 2017. Terpaparnya remaja oleh PMS bisa dipicu oleh kenakalan remaja seperti hubungan seksual pranikah, narkoba, seks bebas yang tentunya berdampak pada kehamilan di luar nikah, putus sekolah, pernikahan dini, aborsi, persalinan berisiko, penyakit menular seksual. Upaya mengantisipasi kenakalan remaja adalah melalui pembentukan Posyandu Remaja. Posyandu Remaja menjadi bagian dari Program ARU (Anak, Remaja dan Usila), sebagai program unggulan Kementerian Kesehatan dan diterapkan di Dinas Kesehatan Kota Surabaya. Program ini mengedepankan pendekatan preventif karena dipusatkan pada kegiatan primary health care (pelayanan kesehatan primer) secara holistik. Penyelenggaraan program ini merupakan hasil kerjasama dengan Puskesmas Benowo Pemerintah Kota Surabaya yang bertujuan untuk membina posyandu remaja melalui pendidikan kesehatan tentang cara menyikapi masalah pada masa pubertas. Kegiatan ini dihadiri oleh 24 remaja binaan Puskesmas Benowo Surabaya, kegiatan pendidikan kesehatan diberikan melalui metode ceramah kombinasi dengan metode visual education (pemutaran video dokumenter) dan diakhir kegiatan dilakukan evaluasi pengetahuan remaja. Hasil kegiatan pengabdian masyarakat menunjukkan remaja mengalami peningkatan pengetahuan tentang cara menyikapi masalah pada pubertas. Kegiatan pembinaan serupa bisa dijadikan sebagai tindakan preventif yang dilakukan secara berkesinambungan serta bisa dikembangkan ke arah skrining kesehatan secara berkala khususnya PMS pada remaja.